2016
DOI: 10.2147/cia.s72436
|View full text |Cite
|
Sign up to set email alerts
|

Orthogeriatric care: improving patient outcomes

Abstract: Hip fractures are a very serious socio-economic problem in western countries. Since the 1950s, orthogeriatric units have introduced improvements in the care of geriatric patients admitted to hospital because of hip fractures. During this period, these units have reduced mean hospital stays, number of complications, and both in-hospital mortality and mortality over the middle term after hospital discharge, along with improvements in the quality of care and a reduction in costs. Likewise, a recent clinical trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 121 publications
1
39
0
6
Order By: Relevance
“…Some authors have reported that multidisciplinary geriatric care reduces hospital mortality and complications (17,18,19). We also believe that ICU monitoring of complicated cases reduces mortality.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Some authors have reported that multidisciplinary geriatric care reduces hospital mortality and complications (17,18,19). We also believe that ICU monitoring of complicated cases reduces mortality.…”
Section: Discussionmentioning
confidence: 71%
“…Although orthogeriatric units have initiated improvements with respect to care of geriatric patients who are admitted to hospitals due to hip fractures since the 1950s, hip fractures are still a serious socio-economic problem in western countries (17).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this relationship could be a possible explanation, even if it does not consider the osteosynthesis group. Other authors have already described increasing age, 7,8,12,13 poor mental status 7,12,14,15 and a higher degree of comorbidity 8 as risk factors for a worse functional outcome in shorter surveying periods (6-12 months). Discussing increased age as a significant factor for a lower Barthel Index score, especially in a long-term follow-up study, seems to be obvious because of the increasing frailty of the aging patients.…”
Section: Discussionmentioning
confidence: 95%
“…8,9 Pre-facture functional impairment seems to be associated with poor function and mobility in shortand mid-term follow up. 7,[10][11][12] Other factors that are associated with poor functional outcome after the different observation periods (6-12 months) are increasing age, 7,8,12,13 living in an institution, 13 poor mental status, 7,12,14,15 female sex, 12 trochanteric fractures, 7 a higher degree of comorbidity 8 and poor functional status after discharge. 13 There is only one retrospective cohort study with functional long-term follow up that reported the Barthel Index 4.9 years after hip fracture.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In order to optimize recovery, the rehabilitation should include an orthogeriatric care model with an interdisciplinary team, using comprehensive geriatric assessment. 4,5 Length of stay (LOS) in the hospital has been reduced over the recent decades, which has contributed to the establishment of home rehabilitation (HR) teams for continuation of the rehabilitation after discharge. 6 The evidence for team-based rehabilitation after hip fracture in the home setting is still limited, but positive effects on ADL and mobility compared with usual inhospital care have been shown.…”
mentioning
confidence: 99%